The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12917-015-0318-8
|View full text |Cite
|
Sign up to set email alerts
|

Skin malformations in a neonatal foal tested homozygous positive for Warmblood Fragile Foal Syndrome

Abstract: BackgroundSkin malformations that resembled manifestations of Ehlers-Danlos-Syndrome were described in a variety of domestic animals during the last century as cutis hyperelastica, hyperelastosis cutis, dermatosparaxis, dermal/collagen dysplasia, dermal/cutaneous asthenia or Ehlers-Danlos-like syndrome/s. In 2007, the mutation responsible for Hereditary Equine Regional Dermal Asthenia (HERDA) in Quarter Horses was discovered. Several case reports are available for similar malformations in other breeds than Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
66
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 42 publications
4
66
0
Order By: Relevance
“…; Monthoux et al . ). A closely related phenotype is equine regional dermal asthenia (HERDA) in horses, which is caused by a variant in the PPIB gene (Tryon et al .…”
mentioning
confidence: 97%
“…; Monthoux et al . ). A closely related phenotype is equine regional dermal asthenia (HERDA) in horses, which is caused by a variant in the PPIB gene (Tryon et al .…”
mentioning
confidence: 97%
“…The mutation which causes Warmblood fragile foal syndrome (Monthoux et al . ), which is another form of EDS, has not been reported in Quarter Horses. Junctional epidermolysis bullosa (JEB) (Frame et al .…”
Section: Differential Diagnosesmentioning
confidence: 95%
“…Trauma in an unaffected horse could certainly cause wounds similar to those seen with HERDA; however, hyperextensible, loose skin and abnormal scarring are not generally present. The mutation which causes Warmblood fragile foal syndrome (Monthoux et al 2015), which is another form of EDS, has not been reported in Quarter Horses. Junctional epidermolysis bullosa (JEB) (Frame et al 1988;Kohn et al 1989;Lieto et al 2002) could be confused with HERDA but it only occurs in neonatal animals and has not previously been reported in Quarter Horses.…”
Section: Differential Diagnosesmentioning
confidence: 99%
“…Hereditary Equine Regional Dermal Asthenia is caused by a missense mutation (c.115G>A) in the peptidylprolyl isomerase B (PPIB) gene [4]. Warmblood Fragile Foal Syndrome is also an autosomal recessive disease, but it affects Warmblood breeds [10][11][12][13][14]. The disease is caused by a missense mutation (c.2032G>A) in the equine procollagen-lysine, 2-oxoglutarate 5-dioxygenase 1 (PLOD1) gene [5].…”
Section: Introductionmentioning
confidence: 99%
“…The disease is caused by a missense mutation (c.2032G>A) in the equine procollagen-lysine, 2-oxoglutarate 5-dioxygenase 1 (PLOD1) gene [5]. Although the PLOD1 mutation has been identified in only one case report [14], there are four other case reports [10][11][12][13] published before the identification of the causative mutation where the animals were suspected to be affected by the same condition [14].…”
Section: Introductionmentioning
confidence: 99%